Družbeni, zgodovinski, moralni in pripovedni vidiki Vorančeve proze - Štuhec, Miran (Jezik in slovstvo, 2010)
The discussion offers an insight into the principal determinants of Prežihov Voranc's literary opus. With the aid of the short stories Kurjak and Samorastniki, the novel Požganica and the travelogue Gosposvetsko polje it highlights the writer's literarisation of social and moral issues, his epic breadth and extraordinary subtlety and his carefully considered narration, as well as his farsightedness in the description of national-political conditions in the Carinthia region of Austria.
Keywords: Prežihov, Voranc; Slovene literature; slovenska književnost; social realism; novel; socialni realizem; romani; short story; social idea; potopis; novele; socialna ideja